An Islamic Legal Review of Profit-Sharing Practices in Shrimp Fishing - Erlangga Erlangga; Haeran; Triyana Wulandari (Zabags Qu Publish, 2025)
This study explores the practice of profit-sharing between boat owners (juragan) and shrimp fishermen in Kampung Laut, Kuala Jambi District, through the lens of Islamic law. Rooted in a traditional system based on verbal agreements and mutual trust, this cooperation reflects a localized adaptation of the mudharabah contract, wherein the juragan provides the capital and the fishermen supply labor. Employing a qualitative descriptive approach, data were collected through interviews, observation, and documentation involving key actors in the shrimp fishing sector. The findings reveal that while the operational model broadly aligns with the principles of mudharabah, several key aspects such as the absence of written agreements, the burden of loss occasionally falling on fishermen, and moral risks like dishonesty diverge from Islamic legal norms. These deviations highlight a gap between local economic practices and the doctrinal requirements of Sharia, particularly regarding justice, transparency, and equitable risk-sharing. Despite these shortcomings, the model remains effective and culturally resilient. This study contributes to the scholarly discourse by bridging empirical field insights with normative Islamic economic thought, offering a critical yet context-sensitive perspective on how Islamic principles are negotiated in real-world fishing economies.